POISONING CASES OF NOXIOUS SUBSTANCES EATEN AS FOOD: A RETROSPECTIVE STUDY AT A TEACHING HOSPITAL IN MALAYSIA - Fong, Xi Kei; Phan, Chia Wei; Noorasyikin Shamsuddin; Liyana Mazni Zulkifli; Tan, Yee Shin; Sabaratnam, Vikineswary (Malaysian Journal of Public Health Medicine, 2021)
There is limited information regarding the epidemiology of food poisoning in Malaysia as the issue of food poisoning is often perceived as not as huge as compared to other poisoning cases like intoxication by drugs and chemicals. Patients who experience severe food poisoning require hospitalisation, aggressive hydration, and some even require antibiotic treatment. In this study, we aimed to determine an overview of food poisoning cases reported in UMMC. A 10-year retrospective study on the poisoning of other noxious substances eaten as food (ICD10: T62.0-T62.9) in the University of Malaya Medical Centre (UMMC) was performed. A total of 23 medical records of patients, admitted from January 2009 to December 2019 were reviewed. The greatest proportion of food poisoning occurred between the ages of 0 and 9 years, with a predominance of the male gender. Malay patients accounted for most food poisoning cases. All cases of poisoning, including a mushroom poisoning case (T62.0), were accidental. The mushroom poisoning case was then carefully reviewed. To conclude, this study revealed that the most common cause involved in the poisoning was unspecified food poisoning, followed by ingestion of poisonous mushroom. Most patients were given symptomatic and supportive treatments. All patients had favourable outcomes and were discharged with full recovery.